L-GLUTAMINE ERADICATES HELICOBACTER PYLORI GASTRITIS: A NOVEL CASE REPORT - O, Balaji; P, Amita (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Helicobacter pylori is the most common infection causing gastrointestinal diseases in the developing countries. It causes oxidative damage to gastric mucosal cells thereby altering the epithelial proliferation of these cells. With proton pump inhibitors and antibiotics being the mainstay in the management of symptoms, preclinical and clinical research is making inroads with novel therapeutic innovations to target the bacterium with the help of antioxidants. Hence, we report the first case of the treatment and eradication of H. pylori using L-glutamine, a sports medicine supplement with high antioxidant potential.